ENTREPRENEURIAL STRATEGIES FOR FORMING THE CUSTOMER POLICY OF MEDICAL LABORATORY NETWORKS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF TERRITORIAL COMMUNITIES (INNOVATIVE ECONOMY, 2026)
Soltys V.M., Chupil Yu.R. ENTREPRENEURIAL STRATEGIES FOR FORMING THE CUSTOMER POLICY OF MEDICAL LABORATORY NETWORKS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF TERRITORIAL COMMUNITIESPurpose. The aim of the article is to substantiate the role of the customer policy of medical laboratory networks in strengthening their entrepreneurial potential and to develop mechanisms for the interaction of network structures with territorial communities.Methodology. The methodological basis of the research is a systemic approach to the study of entrepreneurial activity in the field of healthcare. A complex of general scientific and specialized methods was used to achieve the set objective: PESTEL analysis was applied to assess the macro-environment of laboratory networks; matrix modelling allowed for the development of a “Business-Community Synergy Matrix in the Sustainable Development System”; generalization and systematization methods were used to classify factors influencing customer policy; the graphic method visualized the factors of customer policy development for laboratory networks in communities. The information base consisted of regulatory and legal acts, WHO analytical reports and rating data.Results. It has been proven that under modern crisis challenges, the customer policy of laboratory networks is transforming from a traditional marketing tool into a key factor in ensuring the financial stability of the business. Market dynamics have been analysed, and the necessity for private medical institutions to transition to the Value-Based Healthcare model has been identified. Macro-environment factors have been systematized, allowing for the determination of strategic business responses to various changes (development of public and private partnership models, flexible package offers and loyalty programs). The developed synergy matrix demonstrates the ability of innovative tools (mobile teams, AI analytics) to simultaneously generate commercial income and a positive social effect.Scientific novelty. For the first time, a conceptual approach to forming the customer policy of medical laboratory networks through the lens of three transformation vectors has been proposed: environmental (implementation of “green logistics” digital workflow), social (development of inclusive services and mobile points), and managerial (compliance control, strategic partnership with local self-government bodies). Unlike existing approaches focused on purely marketing tools, this allows for the balanced development of the laboratory network as a socially responsible entity within the ecosystem of the territorial community. The theoretical and methodological foundations of customer relationship management in medical services have been improved by substantiating the transition from a transactional model to the H2H (Human-to-Human) model. Unlike the traditional approach to the patient as an “object of sale” the proposed model is based on the principles of inclusivity, empathy, and personalization, which increases the level of trust in the private diagnostic system and ensures long-term financial stability of the business under wartime challenges. Scientific substantiation of the implementation of ESG criteria into the strategic management of medical entrepreneurship entities has been further developed. This allowed for a detailed analysis of the impact of environmental, social, and managerial factors on the formation of customer policy, contributing not only to the increased competitiveness of networks but also to the fulfilment of the sustainable development goals of territorial communities by enhancing the accessibility and quality of medical diagnostics.Practical significance. The obtained results have high applied value for the management of private medical companies, as they offer ready-made tools for expanding their presence in communities. The proposed developments can be used by local authorities to form regional health programs and create “health maps” based on medical Big Data.Key words: medical laboratory networks, customer policy, entrepreneurial strategies, territorial communities, sustainable development, ESG transformation, medical services market, decentralization.
Keywords: medical laboratory networks; customer policy; entrepreneurial strategies; territorial communities; sustainable development; ESG transformation; medical services market; decentralization